Implementation of Yanbu’a Method in Improving Learning Outcomes to Read Al-Quran in Pondok Pesantren Darul Ulum, Bae, Kudus - Muhayanah, Lina (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
The Yanbu'a method is applied at the Darul Ulum Kudus Islamic Boarding School to improve learning outcomes to read al-Qur’an. This study aims to determine how to learn al-Qur’an using the Yanbu'a method at the Darul Ulum Kudos Islamic Boarding School. This type of research is descriptive and qualitative research. Data collection techniques were carried out through interviews and documents. The data analysis used followed the analysis of Miles and Huberman's model, namely data reduction, data representation and verification. The results of this study indicate that: First, on the basis of active, innovative, creative, effective and interesting learning the Yanbu'a method is adopted at the Darulum Suci Islamic Boarding School. Second, the role of Yanbu language learning at Darul Ulum Islamic Boarding School to study al-Qur’an is very important to improve learning outcomes to read al-Qur’an. Based on the research results, this method can improve students' ability to read al-Qur’an based on makharijul and tajwid letters.